Managing Productivity in the Infrastructure Sector: A Case Study from Indonesia - Eric R. W. Knight; James D. Meade (Institute for Economic and Social Research, 2015)
This paper considers the nature of assessing productivity and effectiveness in infrastructure investment in the context of governments’ increasing investment in new infrastructure. Taking the case of energy infrastructure investment within Indonesia, this paper makes three contributions: (i) develops a model for assessing infrastructure productivity based on landscape, regime and niche-level changes, (ii) suggests the interconnection between these levels based on sequencing multi-level changes over time, and (iii) shows the role of supply and demand side initiatives in enabling new infrastructure investment is evaluated. AbstrakArtikel ini mempertimbangkan sifat dari penilaian produktivitas dan efektivitas pada investasi infrastruktur dalam rangka peningkatan investasi pemerintah pada infrastruktur baru. Dengan menggunakan kasus investasi infrastruktur energi di Indonesia, artikel ini menghasilkan tiga hal: (i) nembangun model untuk menilai produktivitas infrastruktur berdasarkan perubahan dari lanskap, rezim, dan perubahan di level yang tepat, (ii) menunjukkan interkoneksi antar level-level tersebut berdasarkan perubahan multi-level yang berurutan dari waktu ke waktu, dan (iii) menunjukkan peran dari inisiatif sisi penawaran dan permintaan yang memungkinkan investasi infrastruktur baru untuk dievaluasi.Kata kunci: Infrastruktur; Investasi; Produktivitas; Kerangka Perspektif Multi-Level; InovasiJEL classifications: O25; O33; O38